Analysis of women’s empowerment through sustainability stock indices - Cosculluela-Martínez, Carolina; de la Orden de la Cruz, María del Carmen; Díaz-Iglesias, Susana (Investigaciones Feministas (Feminist Research), 2021)
Introduction. The relationship between women’s empowerment and social development is complex and requires a mathematical methodology that permits a more detailed analysis. Objectives. This work aims to provide new evidence of this relationship using the stock indexes linked to the 2030 Sustainable Development Goals and the women’s role in listed companies. The transparency requirements for this type of company make ESG (Environmental, Social, and Governance) corporate policies and the promotion of the role of women more visible, which makes them suitable for academic studies. Methodology. Therefore, several iSTOXX stock indices related to ESG factors of social and governance, and the STOXX® Global Women Leadership Select 30 EUR Index as an indicator of woman empowerment. To estimate this relationship has been used a Vector Error Correction Model methodology that requires a minimum number of assumptions in the variables, and it is not necessary to specify a complete multi-equational structural econometric model. The proposed model determines the significance of the correlations between the series considered, achieving a partial orthogonalization that is sufficient to estimate the searched effects. Results. The results show that women empowerment increases the social and governance performance of listed companies. Conclusion. This new evidence reaffirms the need to maintain active corporate policies to support women’s empowerment.